Kontak Dan Konflik Bahasa Pada Remaja Kampung Dupak: Kajian Sosiolinguistik - Kusuma Wati, Aisyah; Yulianto, Bambang (CV. SINAR HOWUHOWU, 2025)
Language contact and language conflict are fascinating topics within the field of sociolinguistics. In multilingual societies, differences in linguistic backgrounds can lead to both language contact and conflict. This study explores such phenomena among teenagers in Dupak Village, Surabaya. The data were obtained from three teenage informants originating from Madura, Tuban, and Solo, who currently reside in Surabaya. The results reveal how language contact and conflict occur between these minority teenagers and native teenagers of Dupak Village as their interlocutors.